2015
DOI: 10.1002/jhbp.279
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic versus open distal pancreatectomy: is a randomized trial necessary?

Abstract: Laparoscopic approaches exist for most operations traditionally performed using open techniques, and an increasing number of organ resections are being performed laparoscopically. The potential benefits of laparoscopic over the open approach include reduced operative blood loss, fewer surgical complications, shorter hospital stays, and faster recovery times. Cholecystectomy and adrenalectomy are two such examples of organ resections more commonly performed laparoscopically than open in the United States, as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
2
6
0
Order By: Relevance
“…[19]. Our series with 10 cases showed a count of retrieved lymph nodes of 15 (range, [13][14][15][16][17][18][19][20][21],and the R0 resection rate of 100.0%, similar to what have been reported in the literature [5][6][7][8][9][10][11].So whether LRAMPS could achieve better oncological outcomes than laparoscopic conventional DPS or similar…”
Section: Discussionsupporting
confidence: 85%
“…[19]. Our series with 10 cases showed a count of retrieved lymph nodes of 15 (range, [13][14][15][16][17][18][19][20][21],and the R0 resection rate of 100.0%, similar to what have been reported in the literature [5][6][7][8][9][10][11].So whether LRAMPS could achieve better oncological outcomes than laparoscopic conventional DPS or similar…”
Section: Discussionsupporting
confidence: 85%
“…[19]. Our series with 10 cases showed a count of retrieved lymph nodes of 15 (range, [13][14][15][16][17][18][19][20][21],and the R0 resection rate of 100.0%, similar to what have been reported in the literature [5][6][7][8][9][10][11].So whether LRAMPS could achieve better oncological outcomes than laparoscopic conventional DPS or similar oncological outcomes as open RAMPS need more randomized controlled test to con rm. No study to date has shown improved overall survival between RAMPS and standard DP [21][22][23].…”
Section: Discussionsupporting
confidence: 81%
“…Laparoscopic distal pancreatectomy(LDP) has been recognized as a standard technique for benign or borderline malignant neoplasms. The ndings that LDP is associated with lower estimated blood loss, faster recovery than open distal pancreatectomy have increased interest in the procedure [17,18]. Due to recent technological developments, LDP has been expanded to treat PC by LRAMPS.…”
Section: Discussionmentioning
confidence: 99%
“…The term pancreatoduodenectomy is preferred since pancreaticoduodenectomy, although frequently used, is considered grammatically incorrect. 33,34 Similarly, distal pancreatectomy 35,36 and left pancreatectomy 37,38 or central pancreatectomy 39,40 and middle pancreatectomy 41,42 have been used equivalently. The eponymous Whipple surgery 43,44 and Traverso-Longmire surgery 45 or descriptive names such as PPPD, 29,46 SSPPD 47,48 and PRPD 49,50 are used to indicate the extent of gastric or pyloric resection.…”
Section: Discussionmentioning
confidence: 99%